2020
DOI: 10.1177/1049731520946824
|View full text |Cite
|
Sign up to set email alerts
|

Spiritually Informed Interventions and Psychotic Disorders: A Systematic Review of Randomized Controlled Trials

Abstract: Purpose: Including spirituality in the treatment of psychosis is controversial. To determine the effect of incorporating spirituality into treatment, we conducted a systematic review of spiritually informed interventions with persons with psychotic disorders (PPD). Methods: A search of 15 electronic databases was conducted to identify randomized controlled trials that used spiritually informed interventions with PPD. Results: Of 4,317 papers examined, seven studies met eligibility criteria. A narrative review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Given that higher levels of spirituality are endorsed by those persons with serious mental health conditions who are resilient (Mizuno et al, 2016), interventions for people who embrace spirituality should target increasing and capitalizing on their spiritual strengths as key resources for coping with stress related to COVID-19 (Franczak et al, 2016). A recent review of spiritually informed interventions for persons with serious mental health conditions revealed that such approaches are consistently associated with positive outcomes, including lower levels of psychotic symptoms and recovery, and show no evidence of being harmful (Turner & Hodge, 2020). Such interventions involve psychoeducation about the value of spiritual coping and incorporate the person’s spiritual beliefs into the treatment.…”
Section: Resilience Intervention Frameworkmentioning
confidence: 99%
“…Given that higher levels of spirituality are endorsed by those persons with serious mental health conditions who are resilient (Mizuno et al, 2016), interventions for people who embrace spirituality should target increasing and capitalizing on their spiritual strengths as key resources for coping with stress related to COVID-19 (Franczak et al, 2016). A recent review of spiritually informed interventions for persons with serious mental health conditions revealed that such approaches are consistently associated with positive outcomes, including lower levels of psychotic symptoms and recovery, and show no evidence of being harmful (Turner & Hodge, 2020). Such interventions involve psychoeducation about the value of spiritual coping and incorporate the person’s spiritual beliefs into the treatment.…”
Section: Resilience Intervention Frameworkmentioning
confidence: 99%
“…This would help to clarify if one's perceptions are true hallucinations or prevalent in religion, thereby reducing misdiagnosis risk (Adeponle et al, 2012). In a recent systematic‐review, integrating religion‐spirituality into CBTp was more effective than CBTp alone for it validated clients' religious‐spiritual viewpoints rather than dismissing them as maladaptive (Turner & Hodge, 2020). Hence, EIS services could adopt a bio‐psycho‐spiritual‐social‐model within CBTp.…”
Section: Discussionmentioning
confidence: 99%
“…It may be useful to factor in families (e.g. Habib et al, 2015;Ma et al, 2020;Nickels et al, 2016) and religion (Heffernan et al, 2016;Turner & Hodge, 2020) when designing psychosis self-help tools in the Nicaraguan and Latin American context. Future research could develop different versions of CBT-based self-help, and make a comparison of the effectiveness of these tools.…”
Section: Discussionmentioning
confidence: 99%